Forecasting Coconut Production in Indragiri Hilir with Autoregressive Integrated Moving Average Model - Hermiza Mardesci; Maryam Maryam; Khairul Ihwan (Sistemasi: Jurnal Sistem Informasi, 2023)
Indragiri Hilir is one of the districts in Riau Province which is the largest coconut producer in Indonesia. Based on statistical data, total coconut production in Indragiri Hilir was recorded at around 313,396 tons in 2021, but production has decreased from year to year. It is necessary to know the amount of future coconut production, so that a solution can be found so that coconut production in Indragiri Hilir can increase again. The purpose of this research is to find out the estimation or forecasting of coconut production for the next 5 years. This is useful to know the extent of the decline in coconut production during this time, so that a solution can be found. In this study, forecasting the amount of coconut production was carried out using the Autoregressive Integrated Moving Average (ARIMA) method. The Autoregressive Integrated Moving Average (ARIMA) is a model that completely ignores independent variables in making forecasts. Data analysis in this study uses the EViews application as a tool for forecasting. Based on the forecasting results that the amount of coconut production for the next 5 years (2022-2026) is decreasing. If this is allowed to continue, over time Indragiri Hilir will no longer be the largest coconut producer in Riau. The solution given is replanting of damaged and old crop land that needs to be improved. In this case, the government's role is needed in increasing plant replanting programs, especially in smallholder plantations.Keywords: forecasting, coconut, ARIMA, replanting.